Harmonic and Transient Overvoltage Analysis Concerning Capacitor Banks Switching in Yen Son Distribution Grid by using EMTP - Tran, Thanh Son (Old Journal, 2017)
This paper presents the simulation results by using EMTP (Electromagnetic Transient Program) to estimate the effect of harmonic resonance and transient overvoltage due to capacitors switching in the 374E1.14 feeder, Yen Son distribution network, Tuyen Quang province. The simulation results showed that harmonic resonance occurred at the capacitor banks location at Tan Binh substation since 11th harmonic current is presented in this feeder and the capacitor size was 150kVAr. The harmonic voltage distortion factor THD obtained in the simulation was 6.48%. The capacitor sizes, in which harmonic resonance occurs, were then determined to avoid. Transient analysis showed that maximum overvoltage level due to capacitor banks switching achieved 1.94pu. Simulation using 1Ω resistance on bypassing resistors proved that the reduction of the magnitudes of the transients in the voltage and current waves is possible.